Law Enforcement of Election Crimes in Indonesia - Diding Rahmat; Anthon Fathanudien (Universitas Kuningan, 2021)
The election is an election conducted by Indonesian citizens who have the right to vote to choose their representatives who sit in the House of Representatives both central and regional, or the Regional Representative Council, the President, and Vice President as a means of sovereignty people. Elections are carried out in a direct, public, free, confidential and fair manner. While election crimes are prohibited acts such as violating campaign bans, conducting campaigns outside the established schedule, providing incorrect information related to voter registration data, political money, adding, reducing and or changing votes. The purpose of this study was to determine the regulation of election criminal acts in Indonesia and how to enforce the law. Election crime regulations are regulated in Law Number 7 of 2017 Concerning Elections, namely Article 488 through Article 554. Election criminal law enforcement in Indonesia there are 116 cases consisting of 29 cases of money politics, 22 cases of acts harming election participants, 15 cases counterfeiting, 10 cases of campaigning in places of worship or educational institutions, 9 cases of campaigning outside the schedule, 17 cases of campaigning involving banned parties, 7 cases of campaigning using government facilities, 5 cases of destruction of props and 2 cases concerning the election of participants and their data still, then, in general, the implementation has run well even though at the level of implementation there are only weaknesses such as the substance of the regulation and sanctions for election crimes are multiple interpretations along with severe sanctions, from the structure in this case there are still law enforcement officers in this case GAKUMDU, Bawaslu, the police and the police The weaknesses experienced by weaknesses such as in terms of budget, human resources and facilities and infrastructure aside from the side, culture namely the culture of the community which is still low in the awareness of elections in Indonesia, makes violations of election criminal offenses still high.